Implementation of Social Media in Education Sector: A study - Sariyala, Bhagwati; Gopalan, Samir; Shah, Khushbu (Journal of Neonatal Surgery, 2025)
Social media platforms are changing the way businesses operate. The education sector is no exception and is positively impacted by the use of social media sites such as Facebook, LinkedIn, Google+, Instagram, Twitter and Youtube. Recently, many universities and educational service providers are reported to be increasing their use of social media marketing to promote their courses and attract students. Educators are beginning to realize the potential benefits of social media in education. Many departments found that students spend an average of five hours a day on social media. Social media has brought us closer to people in different parts of the world. The use of social media has become part of the business marketing mix. 2011 saw an increase in the use of social media as a marketing channel. Interacting on social platforms has become part of our culture. Social media has provided a platform for people to discuss and grow their knowledge base.